The indirectly generated tainted truth effect: warning is not necessary to worsen the testimony of non-misled persons - Szpitalak, Malwina (Psychology, crime & law, 2017)
The purpose of the present research was to examine the indirectly generated tainted truth effect (TTE). The TTE refers to decreased accuracy on a memory test among persons who are erroneously warned about non-existent misinformation in material that describes an event. It was expected that the TTE would occur even without an explicit warning about misinformation, if one distinctive item of misinformation appeared in postevent material that also contained correct information that was consistent with the original material about the event (indirectly generated TTE: IGTTE). Experiment 1 produced the IGTTE and this effect was replicated in Experiment 2. Experiment 2 showed that the classic and indirect versions of the TTE usually occurred among persons who incorrectly monitored the source of information. Experiment 3 replicated the IGTTE using a procedure that included an additional phase between presenting the original and postevent material - initial testing. When the initial testing procedure was administered in Experiment 3, the TTE was smaller; however, this initial testing procedure had no effect on the IGTTE.